2021
DOI: 10.1530/rep-20-0604
|View full text |Cite
|
Sign up to set email alerts
|

Gene editing to investigate the role of conceptus factors in the establishment of pregnancy in the pig

Abstract: Development of viviparity in mammals required that the placenta evolve as an intermediate interface between the fetus and maternal uterus. In addition to the retention of the fetus and secretion of nutrients to support growth and development to term, it was essential that viviparous species modify or inhibit the maternal immune system from recognizing the semi-allogeneic fetus. Following blastocyst hatching from its zona pellucida, trophoblast differentiation provides the initial communication to the maternal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Nevertheless, elongation and implantation are used to describe the initial stages of placental development in pigs. Although the duration of the preimplantation period is prolonged in the pig, and the type of implantation differs from that of many other species, the initial stages of implantation are common across species and are characterized as the “adhesion cascade for implantation” (Geisert et al, 2021; Johnson et al, 2014; Waclawik et al, 2017; Zang et al, 2021; Zeng et al, 2019). This adhesion cascade begins with shedding of the zona pellucida, followed by elongation of the conceptus trophectoderm.…”
Section: Conceptus and Placental Developmentmentioning
confidence: 99%
“…Nevertheless, elongation and implantation are used to describe the initial stages of placental development in pigs. Although the duration of the preimplantation period is prolonged in the pig, and the type of implantation differs from that of many other species, the initial stages of implantation are common across species and are characterized as the “adhesion cascade for implantation” (Geisert et al, 2021; Johnson et al, 2014; Waclawik et al, 2017; Zang et al, 2021; Zeng et al, 2019). This adhesion cascade begins with shedding of the zona pellucida, followed by elongation of the conceptus trophectoderm.…”
Section: Conceptus and Placental Developmentmentioning
confidence: 99%
“…It has long been proposed that conceptus production of interleukin 1 beta 2 (IL1B2), estrogen (E 2 ), prostaglandin E2 (PGE2) and interferon gamma (IFNG) are critical for conceptus development and implantation. Recently, CRISPR-Cas9 gene-editing technology provides an easy way to test these hypothesis by performing loss-of-function studies in the pig conceptus ( Geisert et al, 2021 ). Inactivation of IL1B2 resulted in failure of rapid conceptus elongation ( Whyte et al, 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Scale bar = 10 mm. approaches (i.e., transcriptomics, proteomics, and metabolomics) to identify deviations of entire pathways on a comprehensive scale, and more recently CRISPR-Cas9 technologies that utilize specific loss-offunction studies to study specific conceptus factors (Geisert et al, 2021), there has been a significant increases in the understanding of the biological processes that regulate the entirety of conceptus elongation.…”
Section: Developmental Hallmarks Of the Peri-implantation Period Of P...mentioning
confidence: 99%
“…Although crosstalk is primarily throught to occur between the uterine endometrium and conceptus during elongation (Ostrup et al, 2011), recent evidence has demonstrated crosstalk mechanisms between the trophectoderm and embryo proper during elongation, illustrating potential paracrine signaling between various cell types of the conceptus to stimulate and progress through elongation (Geisert et al, 2014; Jeong et al, 2016; Valdez Magana et al, 2014). With recent advancement of scientific technology, particularly ‐omics approaches (i.e., transcriptomics, proteomics, and metabolomics) to identify deviations of entire pathways on a comprehensive scale, and more recently CRISPR‐Cas9 technologies that utilize specific loss‐of‐function studies to study specific conceptus factors (Geisert et al, 2021), there has been a significant increases in the understanding of the biological processes that regulate the entirety of conceptus elongation.…”
Section: Developmental Hallmarks Of the Peri‐implantation Period Of P...mentioning
confidence: 99%